Stylistic features of discourse and features of their translation (Texas Journal of Multidisciplinary Studies, 2024)
This article examines scientific and technical transformations covering all aspects of the existence of modern society, as well as the need for specialist translators with practical skills in translating scientific and technical texts related to various fields of knowledge